Education Research: NeuroBytes. (24th August 2021) - Lavette, Laura E.; Miller, Alexandra; Rook, Bobby; London, Zachary; Cook, Calli; Merkler, Alexander E.; Santini, Veronica; Ruff, Ilana Marie; Kraakevik, Jeff; Smith, Don; Anderson, Wayne E.; Johnson, Stacy L.; et al.
Abstract : Objective: To determine whether NeuroBytes is a helpful e-Learning tool in neurology through usage, viewer type, estimated time and cost of development, and postcourse survey responses. Background: A sustainable Continuing Professional Development (CPD) system is vital in neurology due to the field's expanding therapeutic options and vulnerable patient populations. In an effort to offer concise, evidence-based updates to a wide range of neurology professionals, the American Academy of Neurology (AAN) launched NeuroBytes in 2018. NeuroBytes are brief (<5 minutes) videos that provide high-yield updates to AAN members. Methods: NeuroBytes was beta tested from August 2018 to December 2018 and launched for pilot circulation from January 2019 to April 2019. Usage was assessed by quantifying course enrollment and completion rates; feasibility by cost and time required to design and release a module; appeal by user satisfaction; and effect by self-reported change in practice. Results: A total of 5, 130 NeuroBytes enrollments (1, 026 ± 551/mo) occurred from January 11, 2019, to May 28, 2019, with a median of 588 enrollments per module (interquartile range, 194–922) and 37% course completion. The majority of viewers were neurologists (54%), neurologists in training (26%), and students (8%). NeuroBytes took 59 hours to develop at an estimated 77.94/h. Of the 1, 895 users who completed the survey, 82% were "extremely" or "very likely" to recommend NeuroBytes to a colleague and 60% agreed that the depth of educational content was "just right." Conclusions: NeuroBytes is a user-friendly, easily accessible CPD product that delivers concise updates to a broad range of neurology practitioners and trainees. Future efforts will explore models where NeuroBytes combines with other CPD programs to affect quality of training and clinical practice.